PENGALAMAN KUALITAS TIDUR PADA PASIEN HIPERTENSI : STUDI FENOMENOLOGI - Nila Putri Purwandari; Novia Fatimatuzzahroh (Journal Keperawatan, 2023)
Hypertension is one of the leading causes of death and one of the diseases with the highest incidence in the world. Hypertension can be caused by several factors such as age, gender, personality type, genetic factors, obesity, exercise, diet, lifestyle, stress, and sleep patterns. Poor sleep quality is a factor in the occurrence of physical, psychological, environmental and lifestyle problems. The physical problems caused include a decrease in daily activities, weakness, fatigue, decreased endurance, and instability of vital signs, while psychological factors impact depression, anxiety, and difficulty concentrating. Study was to determine the experience of sleep quality in hypertensive patients at the Karanganyar 1 Health Center. The design of this study was qualitative using a phenomenological approach by involving 3 hypertension participants who had poor sleep quality. Three themes that emerged were then used to reflect the objectives of the study, including: 1) perceptions of hypertensive patients about sleep quality 2) problems perceived by hypertensive patients with sleep quality 3) how hypertensive patients deal with sleep quality. All participants experienced poor sleep quality, such as difficulty sleeping, short sleep hours, frequent daytime sleepiness, waking up in the middle of the night, difficulty sleeping again. Participants felt complaints such as dizziness, neck pain, and participants experienced drug dependence.